PEREMPUAN ACEH AWARD: PASANG SURUT GERAKAN PEREMPUAN ACEH DALAM PEMBERDAYAAN PEREMPUAN - Sari, Rosnida (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2018)
This paper looks at the Acehnese women's movement in helping to respect women's work in the grassroots community. This effort was carried out to give recognition and appreciation for women who have dedicated themselves to upholding women's human rights in Aceh, because there are still many people who do not yet know the humanitarian work they have done. The women who were nominated were those who worked since the time of the conflict until now. This voluntary work they do without financial support on a regular basis from the government, although some of them are listed as volunteers in their respective city P2TP2A. The types of cases they handle vary, from domestic violence cases to women's empowerment and society. This research was conducted in the Banda Aceh, Bener Meriah and Central Aceh regions. The research method for this study was in-depth interviews of winners, nominees and implementers of activities shaded by the Ureung Inong Aceh Shura Hall. The results of this study indicate that there are ups and downs in the implementation of this activity. Some of the obstacles that hindered him were the unavailability of funds, weak government commitment and lack of coordination of women's institutions in Aceh in the success of this activity.Keywords: Aceh Women Award, Aceh Women's Movement, Empowerment